Ethnobotanical studies and conservation status of the medicinal flora of Bara Gali Forests, District Abbottabad, Pakistan - Buddin, Shaha; Ibrahim, Muhammad; Ullah, Asad; Dastagir, Ghulam; Bibi, Sadaf; Sara; Ahmad, Imran; Ullah, Inayat; Ahmad, Mushtaq; Khan, Bakhtiar (Ethnobotany Research and Applications, 2024)
Background: An ethnobotanical investigation was conducted in Bara Gali Forests, District Abbottabad, Pakistan, during different seasons of the year 2018. The study area entertaining rich biodiversity and traditional knowledge on medicinal plants, remain understudied, prompting this investigation to document ethnobotanical uses, assess conservation status, and bridge the knowledge gap on the region’s unexplored medicinal flora. Methods: This ethnobotanical survey was conducted by using semi-structured interviews, questionnaire surveys, and field observations. A total of 120 local informants of different age groups and genders representing farmers, herbalists, and traditional healers were selected through purposive sampling. Ethnobotanical indices such as Use Value (UV) and Relative Frequency of Citation (RFC) were used to evaluate the ethnobotanical data. Results: A total of 132 Plant species belonging to 109 genera and 62 families were collected from the research area. Out of 132 species 87 genera and 109 species were dicotyledons followed by, 13 species of Monocotyledons, 6 species of Pteridophytes and 5 species of Gymnosperms. Maximum genera and species in case of dicots were recorded in family Asteraceae i.e., 11 species. Regarding the plant parts used in herbal remedies, leaves were the predominant part with 40 species. The IUCN standard categories revealed that 52 species fell under the category of least concern (LC), 77 species were not evaluated (NE), and 3 species were classified as endangered (EN). To establish their indigenous or exotic status, various floras of the world and the flora of Pakistan were consulted. The findings indicated that 115 species were indigenous, while 17 species were identified as exotic. Conclusions: The region boasts a significant diversity of medicinal plants; however, their abundance has been significantly diminished due to unsustainable utilization and overexploitation. Keywords: Diversity, Ethnobotany, Conservation studies, Vascular plants, Abbottabad, Bara Gali Forests.